Pengaruh dukungan keluarga terhadap kecepatan peyembuhan individu yang sedang sakit - Ilyas, Zakiya Zahro (Maliki Interdisciplinary Journal, 2024)
Family is the first social group in social life, a place of learning, and express itself as a social being in relation to interaction wich its group. Motivation is a form of encouragement both from outside of humans to encourage changes in attitudes and behavior. Family support is a good influence for patients, because family support is given as it is without being artificial. This study aims to provide an overview of the relationship between family support and patient recorvery. The research methods used are quantitative and qualitative methods. Quantitative methods are carried out by sampling techniques questionnaries, while qualitative methods are carried out by descriptive research with literature reviews from varios journals. The result of this study stated that good support from family was proven to accelerate the healing of patients.